Inhibitory test of turmeric leaves extract (Curcuma Longa. L) against the growth of Streptococcus mutans bacterial growth in vitro - Gostry Aldica DOHUDE; Hendry RUSDY; Olivia Avriyanti HANAFIAH; Preetypal Kaur JOHAL (Dentistry Faculty, 2022)
Streptococcus mutans is a bacterium that plays an essential role in forming dental caries. Odontogenic infection is an oral cavity infection that can develop from dental caries if not appropriately treated. Caries treatment can be done with the use of antimicrobial agents. The increasing resistance to antimicrobial drugs has made herbal medicines the choice because they are more effective and less harmful. The community uses turmeric leaves as a cooking spice and treatment for stomach aches in children. Turmeric leaf extract contains flavonoids, tannin, and phenolic antimicrobial active compounds. This research aims to find out if turmeric leaf extract inhibits the growth of the Streptococcus mutans. This study uses a post-test-only control condition approach in a laboratory setting. The concentration of turmeric leaf extract tested was 10%, 15%, and 20% with the positive control (Chlorhexidine 0,2% mouthwash) and negative control (DMSO) with five repetitions. Antibacterial effectiveness test using Kirby-Bauer disc diffusion method. The data analysis using ANOVA showed a p-value of 0.00 on inhibition, which indicates that turmeric leaf extract can suppress the development of Streptococcus mutans. The average inhibition zone obtained was 8.7 mm at a concentration of 10%, at a concentration of 15% at 9.5 mm, and at a concentration of 20% at 8.54 mm. This research concludes that turmeric leaf extract can inhibit the proliferation of Streptococcus mutans bacteria KEYWORDS: Turmeric Leaf, Streptococcus mutans, Antibacterial